Efficacy of Dimethyl Trisulfide on the Suppression of Ring Rot Disease Caused by Botryosphaeria dothidea and Induction of Defense-Related Genes on Apple Fruits - Sun, Meng; Duan, Yanxin; Liu, Jun Ping; Fu, Jing; Huang, Yonghong (Frontiers in Microbiology, 2022)
Apple ring rot caused by Botryosphaeria dothidea is prevalent in main apple-producing areas in China, bringing substantial economic losses to the growers. In the present study, we demonstrated the inhibitory effect of dimethyl trisulfide (DT), one of the main activity components identified in Chinese leek (Allium tuberosum) volatile, on the apple ring rot on postharvest fruits. In in vitro experiment, 250 μL/L DT completely suppressed the mycelia growth of B. dothidea. In in vivo experiment, 15.63 μL/L DT showed 97% inhibition against the apple ring rot on postharvest fruit. In addition, the soluble sugar content, vitamin C content, and the soluble sugar /titratable acidity ratio of the DT-treated fruit were significantly higher than those of the control fruit. On this basis, we further explored the preliminary underlying mechanism. Microscopic observation revealed that DT seriously disrupted the normal morphology of B. dothidea. qRT-PCR determination showed the defense-related genes in DT-treated fruit were higher than those in the control fruit by 4.13 to 296.50 times, which showed that DT inhibited apple ring rot on postharvest fruit by suppressing the growth of B. dothidea, and inducing the defense-related genes in apple fruit. The findings of this study provided an efficient, safe, and environment-friendly alternative to control the apple ring rot on apple fruit.